Pengaruh Experiental Marketing Dan Servicescape Terhadap Loyalitas Konsumen (Studi Kasus : Di Setia Coffee & Billiard Medan Helvetia) - Putri, Farhana; Suryani, Wan (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
This study aims to determine the effect of Experiential marketing and Servicescape on consumer loyalty at Setia coffee Billiard Medan Helvetia. This type of research is associative with a quantitative approach. The number of samples in this study amounted 74 respondents taken from 290 total consumer population of Setiacoffee Billiard Medan Helvetia from January 2023 - April 2023. Based on partial t-test results, the experiential marketing variable has a positive and significant influence on customer loyalty. For the t-test on the Servicescape variable partially too has a significant influence on the Customer Loyalty variable. Based on the Ftest, it was found that the experiential marketing variable and the Servicescape variable simultaneously had a positive and significant effect on Consumer Loyalty. The Adjusted R-Square value obtained was 0.855. By calculating the Determination Coefficient R2 x 100%, a result of 85.5% of the Consumer Loyalty variable can be explained by the Experiential Marketing variable (X1) and the Servicescape variable (X2), the remaining 14.5% is influenced by other factors not explained in this study